2021
DOI: 10.30521/jes.817879
|View full text |Cite
|
Sign up to set email alerts
|

Proton exchange membrane fuel cell fault and degradation detection using a coefficient of variance method

Abstract: Proton exchange membrane fuel cell is a clean energy generator as it emits water as a by-product. The fuel cell has various applications in stationary power generation and transportation. However, there is a need to improve durability for transportation applications. Fuel cell durability is limited as its performance degrades over a period due to aging, and fault conditions. In this study, we have compared fuel cell performance by using a new cell, and an aged cell. Degradation due to aging is experimented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…CV measures the relative variability of the parameters and can be used to compare the voltage degradation of a PEMFC for a given current. The coefficients of variance for the fuel cell output voltage CV V , the current density CV CD , and the cell power CV P were calculated for aged cells and cells operating in fault conditions [48]. The experimental results showed that the CV values could differentiate the degradation performance.…”
Section: A Coefficient Of Variancementioning
confidence: 99%
See 3 more Smart Citations
“…CV measures the relative variability of the parameters and can be used to compare the voltage degradation of a PEMFC for a given current. The coefficients of variance for the fuel cell output voltage CV V , the current density CV CD , and the cell power CV P were calculated for aged cells and cells operating in fault conditions [48]. The experimental results showed that the CV values could differentiate the degradation performance.…”
Section: A Coefficient Of Variancementioning
confidence: 99%
“…Wavelet and its transform are useful to analyze the time and frequency domains of a signal [53]. Equation (8) shows a "mother" wavelet or a wavelet basis function:…”
Section: Wavelet Transformmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the durability of fuel cells is limited, as their performance degrades over time due to aging and fault conditions, as stated in Ref. [4]. Since the invention of photovoltaic cells, various prototypes of solar cars have been designed in universities and industrial environments [5].…”
Section: Introductionmentioning
confidence: 99%